2023
DOI: 10.1371/journal.pone.0283542
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence and co-infection of high-risk Human Papillomavirus genotypes among unvaccinated young women from Paraguay

Abstract: Paraguay launched a human papillomavirus (HPV) vaccination program in 2013, so virological surveillance is important for measuring the impact of HPV vaccines. This study aimed to estimate the type-specific HPV frequency in unvaccinated sexually active women aged 18–25 years in the metropolitan area of Asuncion as a baseline for monitoring the HPV vaccination program. This study included 208 women, attending the Central Laboratory of Public Health between May 2020 and December 2021, were invited for testing thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…In a previous study conducted by our research group, representing the primary comprehensive report on HPV prevalence and genotypic distribution in Paraguay, we substantiated the existence of HPV types targeted by contemporary vaccines circulating among unvaccinated, sexually active young women. This established baseline serves as a pivotal tool for evaluating the impact of the national HPV immunization program, facilitating the estimation of both vaccine and non-vaccine HPV type prevalence [ 66 ]. Understanding the risk behaviors associated with HPV infection is important for prevention and public health.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study conducted by our research group, representing the primary comprehensive report on HPV prevalence and genotypic distribution in Paraguay, we substantiated the existence of HPV types targeted by contemporary vaccines circulating among unvaccinated, sexually active young women. This established baseline serves as a pivotal tool for evaluating the impact of the national HPV immunization program, facilitating the estimation of both vaccine and non-vaccine HPV type prevalence [ 66 ]. Understanding the risk behaviors associated with HPV infection is important for prevention and public health.…”
Section: Discussionmentioning
confidence: 99%
“…An overall prevalence of HPV infection of 31.1% was found, which is within a wide range of prevalence reported by other studies in Colombia: Torrado et al [ 17 ] reported 10% in the lower income strata of the mestizo population in a Colombian city; Angarita & Forero [ 9 ] found 47.4% in one group of Indigenous population; Camargo [ 11 ] found 49.6% in five Colombian cities, and Puerto et al [ 10 ] found 60.3% in women aged 18 to 25 years in Bogota. In other Latin American countries, Carrión et al [ 18 ] reported a prevalence of 34% in an Ecuadorian Indigenous population, Martorell et al reported 35.4% in a Peruvian Indigenous population [ 19 ] and Bobadilla et al [ 20 ] in Paraguay reported a prevalence of 54.8%. This variation is found throughout the Latin American region as described by Moya and Rojas [ 21 ], who reviewed 39 publications in which HPV infection prevalence ranged from 6.7% to 82.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in young (under 25 years), unvaccinated, and sexually active Latin American women reported a high prevalence of HPV (greater than 50%); for example, in Paraguay, the prevalence was 54.8% [ 84 ], in Brazil 54.6% [ 85 ], in Colombia it was 60.3% [ 86 ], and in Argentina it was 56.3% [ 87 ]. By contrast, studies carried out on women who attend routine checkups and are over 25 years old found that this percentage is lower, as is the case of the ESTAMPA subcohort study realized in Argentina, Colombia, Costa Rica, Honduras, Paraguay, and Uruguay when only 13% of samples were HPV-positive [ 88 ].…”
Section: Hpv and Cervical Cancer In Latin Americamentioning
confidence: 99%
“…The implementation of HPV vaccines in this region has markedly improved vaccine availability and accessibility since the late-2000s. The majority of the Latin American countries use the tetravalent vaccine; however, some countries such as Paraguay and Argentina could prevent around 38% of HPV with the nonavalent vaccine ( Table 1 ), which is significantly higher than expected with the quadrivalent vaccine (13% and 22.5%, respectively) [ 84 , 87 ]; therefore, the nonavalent vaccine is expected to be available in the upcoming years. Unfortunately, despite these endeavors, the region is falling behind the goal of achieving 90% coverage with two doses of the HPV vaccine for girls by age 15 by 2030 [ 12 , 130 ].…”
Section: Impact Of Hpv Vaccination In La and Challenges In Its Implem...mentioning
confidence: 99%
See 1 more Smart Citation